Etika Al-Mashlahah: Studi Pemikiran Moral Mohammad Abed Al-Jabiri - Achmad Bahrur Rozi (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2020)
The point of this study is the thought of Muhammad Abed al-Jabiri about the moral concept in Islam. Al-mashlahah, according to al-Jabiri, is the moral principle of Islam. Al-mashlahah represents the pure principle of Islamic ethics stemming from al-Qur’an and as-Sunnah. This theory based on the principle of utility; good and ugly determined by consequence of the act, non-action itself. Worthwhile action in al-mashlahah category must be relied on universal of syari’at (taking care of religion, soul, clan, properties, and mind). Al-mashlahah woke up above the principle of compatibility between mental activity and texts. Al-mashlahah does not characterizes secular and therefore can be made alternatively to Utilitarianism.